Candida lusitaniae as an Unusual Cause of Recurrent Vaginitis and its Successful Treatment With Intravaginal Boric Acid - Neil S. Silverman; Margie Morgan; W. S. Nichols (Hindawi Limited, 2001)
Increasing use of short-course antifungal therapies in patients with recurrent vulvovaginitis may enable the emergence of less-common, more resistant yeast strains as vaginal pathogens. We report the case of a patient with chronically symptomatic and repeatedly treated vaginal candidiasis whose infection was attributable to Candidalusitaniae, a previously unreported cause of candidal vaginitis .